Moderating Effect of Ownership Concentration on the relationship between Corporate Social Responsibility and Earnings Management: Evidence from China - SONG, Yixuan (2020)
Recent financial scandals have shown that earnings management has seriously damaged the interests of stakeholders, while the importance that a company pays to stakeholders is a manifestation of its corporate social responsibility. This paper mainly studies the relationship between corporate social responsibility and earnings management and considers the influence of the ownership structure, which has both theoretical and practical significance in improving the level of corporate governance. This research selects 555 companies in the report released by RANKINS and CSMAR from 2012 to 2018 and uses STATA 16.0 to examine the relationship. The possible impact of equity concentration on CSR-EM is further analysed. The results demonstrate that corporate social responsibility is negatively associated with earnings management and it has a stronger adverse influence on real earnings management when compared with accrual earnings management. As the moderating variable, ownership concentration has positively adjusted the negative link of CSR-EM. It is suggested that companies should take ownership concentration into consideration when organizing the firm. When the shareholding is too concentrated, the company may fulfill its social responsibility for speculative purposes, and the possibility of earnings manipulation will increase. The contribution of this paper is twofold. The use of moderating variable enriches the literature among corporate social responsibility, earnings management and ownership concentration, which makes the research more in-depth. In addition, as the biggest developing financial market, China faces severe agency conflicts. All industries in China are taken as the research sample, which makes the results more realistic.